Challenges in quantum key distribution: A review - Hong, K.W. (Association for Computing Machinery, 2016)
Quantum computing is essentially exploiting and harnessing the laws of quantum mechanics to process information. With it, rise the era of a new cryptosystem that has the potential to be unconditionally secure which is known as quantum cryptography. Quantum cryptography uses the properties of quantum mechanics to develop an unbreakable cryptosystem that can never be compromised. Quantum key distribution (QKD), which is an area in quantum cryptography, provides a way for distribution of secure key between two parties. Some of the existing QKD protocols include BB84 protocol, B92 protocol, SARG04 protocol, E91 protocol and many more. In this paper, the trends and challenges in Quantum Key Distribution is reviewed. Â© 2016 ACM.